Diabetes in Asian Indians—How much is preventable? Ten-year follow-up of the Chennai Urban Rural Epidemiology Study (CURES-142). Issue 2 (August 2015) - Anjana, Ranjit Mohan; Sudha, Vasudevan; Nair, Divya H.; Lakshmipriya, Nagarajan; Deepa, Mohan; Pradeepa, Rajendra; Shanthirani, Coimbatore S.; Subhashini, Sivasankaran; Malik, Vasanti; Unnikrishnan, Ranjit; Binu, Valsalakumari S.; Patel, Shivani A.; et al.
Highlights The PAR for diabetes was assessed in a representative urban Indian population. 1376 individuals from Chennai (South India) were followed up after 10 years. 80% of the risk for diabetes could be explained by five modifiable factors. Translation of this information could help slow down the epidemic of diabetes.